Ectopic Expression of Gastrodia Antifungal Protein in Rice Enhances Resistance to Rice Sheath Blight Disease - Junkai Zhu; Xiang Xue; Ran Ju; Jianhua Zhao; Fen Liu; Xian Han; Yu Yan; Yu Wang; Zhiming Feng; Dongmei Lin; Zongxiang Chen; Yiqin Wang; et al. (Journal of Fungi, 2023)
Sheath blight (ShB) disease, caused by Rhizoctonia solani Kühn, is one of the most serious rice diseases. Rice breeding against ShB has been severely hindered because no major resistance genes or germplasms are available in rice. Here, we report that introduction of Gastrodia antifungal protein (GAFP) genes from Gastrodia elata B1 into rice significantly enhances resistance to rice ShB. Four GAFP genes were cloned from G. elata B1, and all displayed a strong ability to inhibit R. solani growth in plate assays. Two versions, with or without a signal peptide, for each of the four GAFP genes were introduced into XD3 and R6547 rice cultivars, and all transgenic lines displayed stronger ShB resistance than the corresponding wild-type control in both greenhouse and field conditions. Importantly, GAFP2 showed the highest ShB resistance; GAFPs with and without its signal peptide showed no significant differences in enhancing ShB resistance. We also evaluated the agronomic traits of these transgenic rice and found that ectopic expression of GAFPs in rice at appropriate levels did not affect agronomic traits other than enhancing ShB resistance. Together, these results indicate that GAFP genes, especially GAFP2, have great potential in rice breeding against ShB disease.